Implementasi Program Manajemen Risiko Keamanan Pangan Bertahap pada Industri Pangan Steril Komersial di Yogyakarta - Tyas Setyaningsih; Wahyu Sulistiadi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Changes in consumer demand for convenient food have spurred the development of commercially sterile food products produced by micro and small enterprises (MSEs). However, commercially sterile food carries the risk of botulism, which can lead to illness or even death. This risk has prompted the government to issue an Indonesian Food and Drug Authority Regulation Number 10 of 2023, which outlines the implementation of the Food Safety Risk Management Program (RMP) in processed food production facilities. This regulation requires MSEs to adopt a phased RMP to ensure food safety. This research aims to assess the performance of RMP implementation among MSEs. A qualitative approach was used, incorporating data from in-depth interviews, observations, and document reviews. The results indicate that budgets, costs, and incentives were inadequate in terms of resources. "Budgets" refers to the Indonesian Food and Drug Authority's budget to implement the policy, while "costs" refers to the expenses MSEs incur to comply with the policy. The research also identified weaknesses in the implementation characteristics, particularly in the availability of human resources (HR) and standard operating procedures (SOPs). The Indonesian Food and Drug Authority’s HR capacity is only 59.8% met, and the availability of SOPs among MSEs remains low. The study concluded that the performance of policy implementation achieved only 48%, due to the absence of documented policy targets, lack of resource support, and insufficient HR and SOP availability. To improve the effectiveness of implementation, it is recommended to set clear performance targets, adjust budgets, provide incentives, and establish SOPs that MSEs can adopt.